Transcriptomics and proteomics reveal genetic and biological basis of superior biomass crop Miscanthus. Issue 1 (December 2017) - Sheng, Jiajing; Zheng, Xingfei; Wang, Jia; Zeng, Xiaofei; Zhou, Fasong; Jin, Surong; Hu, Zhongli; Diao, Ying
Abstract Miscanthus is a rhizomatous C4 grass which is considered as potential high-yielding energy crop with the low-nutrient requirements, high water-use efficiency, and capability of C mitigation. To better understand the genetic basis, an integrative analysis of the transcriptome and proteome was performed to identify important genes and pathways involved in Miscanthus leaves. At the transcript level, 64, 663 transcripts inM .lutarioriparius, 97, 043 inM .sacchariflorus, 97, 043 inM .sinensis, 67, 323 inM .floridulus and 70, 021 inM . × giganteus were detected by an RNA sequencing approach. At the protein level, 1964 peptide-represented proteins were identified and 1933 proteins differed by 1.5-fold or more in their relative abundance, as indicated by iTRAQ (isobaric tags for relative and absolute quantitation) analysis. Phylogenies were constructed from the nearly taxa of Miscanthus. A large number of genes closely related to biomass production were found. And SSR markers and their corresponding primers were derived from Miscanthus transcripts and 90% of them were successfully detected by PCR amplification among Miacanthus species. These similarities and variations on the transcriptional and proteomic level between Miscanthus species will serve as a resource for research in Miscanthus and other lignocellulose crops.